The decline and fall of the British Empire, 1781-1997 - Brendon, Piers (New York : Alfred A. Knopf, 2008)
After the American Revolution, the British Empire appeared doomed. But over the next 150 years it grew to become the greatest and most diverse empire the world has ever seen--from Canada to Australia to China, India, and Egypt--seven times larger than the Roman Empire at its apogee. Yet it was also fundamentally weak, as Piers Brendon shows in this panoramic chronicle. Run from a tiny island base, it operated on a shoestring with the help of local elites. It enshrined a belief in freedom that would fatally undermine its authority. Spread too thin, and facing wars, economic crises, and domestic discord, the empire would vanish almost as quickly as it appeared. Within a generation, it collapsed, sometimes amid bloodshed, leaving unfinished business in Rhodesia, the Falklands, and Hong Kong. Above all, it left a contested legacy: at best, a sporting spirit, a legal code, and a near-universal language; at worst, failed states and internecine strife.--From publisher description.
Maps on endpapers.
"Originally published in Great Britain by Jonathan Cape, London"--T.p. verso.
Includes bibliographical references (p. [665]-759) and index.
Keywords: Commonwealth (Organization) -- History; Imperialism -- History; Great Britain -- Colonies -- History; Commonwealth countries -- History; Great Britain -- Civilization